Free fire - Box, C. J. (Box, C. J. Joe Pickett novel., 2008)
Having recently lost his job as a Wyoming game warden, Joe Pickett is recruited by the devious governor Rulon to oversee a murder investigation involving a confessed killer and overlapping jurisdictions that enabled the man's release.